(untitled) - Saadiah binti Mohd
This study aims to evaluate the practice of online fatwas in Malaysia. In this world of borderless information and technology world, fatwa's resources have spread unlimitedly via internet. Indeed, dissemination of the fatwa via internet has a few things to be considered such as some of these fatwa may be done by those who are not expert in issuing fatwa. This may lead to false fatwa as they talk without knowledge and not following the requirements in issuing fatwa. It will create confusion in the Muslim community. In order to provide general overview of fatwa websites in Malaysia, this paper has studied large number of fatwa websites in Malaysia. Only three websites have been selected to be analysed in great detail. The selected websites are JAKIM website, Selangor's mufti website and Zaharuddin.net website which is an individual website. This study adopts both observation and analytical methods. Findings of this study reveals that there are pro and cons of practising online fatwa. On top of that, this study also has discovered that the practise of online fatwa in Malaysia is less developed as compared to online fatwa in Middle East. Even though there are some authoritative websites on online fatwa in Malaysia, yet further improvement is necessary in order to be more prevalent and beneficial, especially for Muslim in Malaysia.